Assistance process blood cockle (Anadara granosa) based meatballs as local food to prevent anemia in adolescent girls - Asniwati Zainuddin; Margaretha Solang; Yuliana Retnowati; Syam S. Kumaji; Muh. Nur Akbar; Widya Rahmawaty Saman; Budy Santoso; Eka Zahra Solikahan; Eman Rahim (University of Merdeka Malang, 2024)
Assistance in processing local food based on blood cockle (Anadara granosa) can support the anemia prevention program for young women towards a stunting-free Gorontalo. The number of participants included was 20, it's made up of two craft teachers and two school managers. The participants came from SMAN 1 Tilango, SMAN 1 Batudaa Pantai, SMAN 1 Biluhu, SMAN 1 Dungaliyo, and SMAN 1 Pulubala. It involves 5 students from Gorontalo State University who participated in the MBKM research program. The purpose of this activity is for teachers and school canteen operators to gain knowledge about the processing of blood cockle meatballs and use them as potential for the development of local food products to prevent anemia in young women. The importance of innovation in local food processing, such as introducing new technology and developing healthier and more sustainable products. Activities are carried out using five methods, namely lecture, question-and-answer, discussion, practice, and evaluation methods. The result of this service activity was that the participants received the training material and received a positive response. Most participants stated that this activity helped them to innovate and develop their businesses in terms of diversifying local food processing.